Understanding Prevention Networks in a Local Government Area: Insights From a Social Network Analysis Among Western Australian Nutrition, Physical Activity, and Obesity Prevention Programs - Jancey, Jonine; Vidler, Abbie-Clare; Leavy, Justine; Chamberlain, Dan; Riley, Therese; Pollard, Christina; Milligan, Megan; Blackford, Krysten (SAGE, 2021)
This study aimed to use systems thinking tools to understand network relationships to inform discussions, policy, and practice to improve nutrition, physical activity, and overweight/obesity prevention activities in a Western Australian local government area. An audit of nutrition, physical activity, and obesity prevention activities was conducted, and identified organizations were invited to participate in an organizational network survey. Social network analysis (SNA) determined the extent to which organizations shared information, knowledge, and resources; engaged in joint program planning; applied for and shared funding; and identified operational barriers and contributors. SNA data were mapped and analyzed using UCINET 6 and Netdraw software. Five organizations within the network were identified as core; the remainder were periphery. The strongest networks were sharing information, and the weakest was funding. The connections were centralized to one organization, enabling them to readily influence other organizations and network operations. Remaining organizations indicated limited partnership across the networks. Strengthened collaborations and partnerships are essential to health promotion, as they extend reach and organizational capabilities. This study provides a process for undertaking network analysis, identifying leverage points to facilitate communication and information sharing, and reorienting of collaborations and partnerships to consolidate scarce resources and act strategically within a bounded area. There is a need for stronger relationships between organizations and a reorientation of partnerships to facilitate resource sharing within the local government area, to improve nutrition, physical activity, and obesity prevention practices. SNA can assist in understanding organizational prevention networks within a bounded area to support future planning of practices and policy.